Effectiveness of Educational Intervention on Knowledge & Attitude about MTP Act 1971 among Apparently Healthy Reproductive Age Group Population Visiting A Tertiary Care Centre, Puducherry (Indian Journal of Forensic Medicine & Toxicology, 2020)
Medical termination of Pregnancy Act is one such Act which was brought by the Indian Government tostreamline the process of abortions conducted in India. Its rules were framed for the first time in 1972,amended in 1975, 1977, 2003, and 2009 and recently in October 2014. The main motive of passing suchbills was to decrease the female foeticide rate, decrease the maternal mortality rate, improve the health ofthe mother and the newborn and to avoid unwanted and illegal abortion practises. In spite of these measuresfrom the government, more than 5000 deaths due to unsafe abortions take place every year in our country.The main cause of such death related to abortion is mainly due to the ignorance of the general public towardsabortion. Majority of the women, not only in the rural parts, but also in the urban regions does not know aboutthe mere existence of the MTP law. Hence this study was aimed to estimate the level of awareness about theMTP Act among the apparently healthy reproductive age group public, visiting the hospital and apart from it,we also educate them regarding the MTP Act and its uses. Among our participants the minimum age reportedwas 20 and the maximum age was 45. Out of total 220, female accounted to 63.2% and male 36.8%. Amongthem married people accounted for 69.5%, unmarried 28.2% and others were 2.3%. 42.3% of people hadhistory of abortion their family but 64% of people doesn’t know whether the conducted abortion was a legalor a illegal one. Eleven questions were asked to the participants and an initial assessment of their knowledgewas done with the help of a questionnaire. After this immediately, educational intervention was carried outabout the law and after a gap period of one month the participants were asked the same questions as beforeusing telecommunication device and their knowledge was tested.